2008
DOI: 10.1002/dc.20827
|View full text |Cite
|
Sign up to set email alerts
|

Indications for thyroid FNA and pre‐FNA requirements: A synopsis of the National Cancer Institute Thyroid Fine‐Needle Aspiration State of the Science Conference

Abstract: The National Cancer Institute (NCI) sponsored the NCI Thyroid Fine-Needle Aspiration (FNA) State of the Science Conference on October 22-23, 2007 in Bethesda, MD. The 2-day meeting was accompanied by a permanent informational website and several on-line discussions between May 1 and December 15, 2007 (http://thyroidfna.cancer.gov). This document summarizes the indications for performing an FNA of a nodule discovered by physical examination or an imaging study; the indications for using ultrasound versus palpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
106
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 100 publications
0
106
0
7
Order By: Relevance
“…Therefore, a multidisciplinary conference was held at the National Cancer Institute in Bethesda, Maryland, in October 2007, and the proceedings were published in June 2008. [1][2][3][4][5][6] Ultimately, a uniform, 6-tiered reporting system was proposed with defined diagnostic categories, standardized nomenclature, and predictive risk of malignant outcomes for each diagnostic category. 7,8 Since the BSRTC was introduced, the ''atypia of undetermined significance or follicular lesion of undetermined significance'' (AUS/FLUS) category has received significant attention within the cytology literature, and it has been the most controversial.…”
mentioning
confidence: 99%
“…Therefore, a multidisciplinary conference was held at the National Cancer Institute in Bethesda, Maryland, in October 2007, and the proceedings were published in June 2008. [1][2][3][4][5][6] Ultimately, a uniform, 6-tiered reporting system was proposed with defined diagnostic categories, standardized nomenclature, and predictive risk of malignant outcomes for each diagnostic category. 7,8 Since the BSRTC was introduced, the ''atypia of undetermined significance or follicular lesion of undetermined significance'' (AUS/FLUS) category has received significant attention within the cytology literature, and it has been the most controversial.…”
mentioning
confidence: 99%
“…If the patient is taking an anticoagulant or antithrombotic, stopping the medication for 3 -10 days is recommended before and after US-FNA (4,5,9,11,17,18). However, performing US-FNA in patients taking anticoagulant or antithrombotic remains controversial and lacking in evidence, such as randomized controlled study (2,4,7,9,16,33). A recent study of 593 patients who underwent US-FNA on a total of 788 neck lesions reported no significant differ- ences in hematoma formation between patients who were on antithrombotic medications and those who were not (16).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the hemorrhage complication rate was not significantly different between the two techniques. Hence, the choice between the capillary sampling technique and FNA with suction may depend on operator preference (5,9,41). If a nodule is largely cystic or predominantly cystic, sampling should be done in the residual solid component after aspiration of the fluid component (5,11,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Familial history of thyroid cancer, a low dietary iodine intake, younger age, higher thyrotropin levels, and micro-calcifications within the nodules are considered to be the predictors of malignancy (Othman et al, 2009;Yang et al, 2011;Xhaard et al, 2014). With the improvement in ultrasound (Phuttharak et al, 2009;Cheng et al, 2013;Wu et al, 2013), thyroid FNA (Cibas et al, 2008) and cytopathology reporting system update (Cibas and Ali, 2009), many patients do not need to undergo thyroidectomy to obtain confirmatory diagnosis of thyroid nodules. According to the recent guideline from American Thyroid Association (ATA) (American Thyroid Association Guidelines Taskforce on Thyroid et al, 2009), thyroid FNA under the guidance of ultrasound is the essential mainstay step when making the diagnosis of thyroid nodules (Frates et al, 2006;Yassa et al, 2007;Cheng et al, 2013;Gupta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%